Persistently Present, Yet Invisible? Exploring the Experiences of High-Achieving Black Students in the Greater Toronto Area - George, Rhonda C. (Canadian Journal of Education / Revue canadienne de l'éducation, 2023)
Through employing critical race theory, seen-invisibility, and circuits of dispossession as theoretical frames, this article complicates discourses around equity and Black student achievement by examining the underexplored experiences of high-achieving Black Canadian students in the Greater Toronto Area (GTA). Drawing on focus group data with four adolescent participants, the study finds that they experienced violent forms of racialization in their educational environments through a lack of physical, social, and intellectual space to exist as both Black and high-achieving. This rendered them persistently present due to their race, yet invisible in the perceptions of their intellect.Central to this article is an articulation, unpacking, and thus granular analysis of the particular ways that racialization can operate within education systems to still marginalize Black students and erect complex barriers––even when they demonstrate strong academic performance. These emerging insights inform a need for a broader and more holistic understanding of Black Canadian student experiences and a rethinking of intervention and resistance strategies.